Saúde mental e sofrimento psíquico na perspectiva de adolescentes - Gasparini, Danieli Amanda (2022)
There is not just one way to be adolescent, therefore, the bodily and psychological changes that may happen in this period of life must be considered from the socioeconomic, historical and cultural context in which the individual is inserted. Based on the analysis of the most recent literature, it is possible to perceive a concern about the adolescents mental health, since the rates of psychological distress in this population are on the rise. On the other hand, there is an indication of the need for more studies that address the issue of mental health based on the experiences of adolescents themselves, considering their perspective on the knowledge construction about themselves. Thus, this study objective was to identify the understanding of adolescent high school students about mental health and psychological distress. The methodology used was qualitative and exploratory. The participants were 15 adolescent-high school students from public and private schools in a country city of the state of São Paulo, identified by the “snowball” type sampling. The data acquisition was carried out in a virtual environment, through a video call application, through the technique of graphic elucidation and open interview. Data were recorded, transcribed and analyzed using the thematic analysis technique. From the results analysis, it was possible to perceive that the adolescents understand that mental health is the sensation produced when one can do something pleasurable, which generates well-being, but is also related to the feelings and emotions that emerge from everyday events, and that it negatively impacts the reality of the subjects when it is impaired. The participants also addressed what they identified as favoring mental health. As, for example, having a support network (friends and family) and carrying out meaningful activities, while conflicts with parents/guardians and personal characteristics (relating difficulty, dealing with frustrations) were one of the indicated situations that harm mental health. About psychic suffering, their speeches were based on their own experiences, from living with people who go through this phenomenon and from what they have imagined this condition to be, highlighting the understanding that adolescents who suffer psychically have feelings of inferiority, loneliness, insecurity, loss of interest in dayli activities and difficulty in accessing help. The COVID-19 Pandemic was indicated as harmful to the mental health of adolescents, due to the difficulties that this condition caused in their daily activities and relationships. The results produced by the participants referred to the discussion about how much the theme of mental health and psychic suffering seem to be present in this population experiences, since the subjects were treated with familiarity and from different dimensions. The findings contribute with elements of a reflective and practical nature, that may collaborate with the development of care and mental health promotion strategies for this population that are more participatory and contextualized to their needs.